2020
DOI: 10.1111/acem.14101
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Department Trigger Tool: Validation and Testing to Optimize Yield

Abstract: Objective: Recognized as a premier approach for adverse event (AE) detection, trigger tools have been developed for multiple clinical settings outside the emergency department (ED). We recently derived and tested an ED trigger tool (EDTT) with enhanced features for high-yield detection of harm, consisting of 30 triggers associated with AEs. In this study, we validate the EDTT in an independent sample and compare record selection approaches to optimize yield for quality improvement. Methods: This is a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The prevalence of AE detected in our study is greater than that reported in studies on AE 17 but similar to that reported in studies where the trigger methodology was used in 7-40% of hospitalized patients 20 .…”
Section: Adverse Eventssupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of AE detected in our study is greater than that reported in studies on AE 17 but similar to that reported in studies where the trigger methodology was used in 7-40% of hospitalized patients 20 .…”
Section: Adverse Eventssupporting
confidence: 87%
“…For some of them the nal model included those with a PPV greater than 5% , 19 . In others a subsequent study was performed for its validation by means of calculating false negatives in a random sample 20 . Some works report the review of trigger histories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the different validation methodologies of the “Trigger Tool”, it should be noted that several studies have been performed in other specialties [ 17 19 ]. Some works have also published results on optimization of the tool in different areas.…”
Section: Discussionmentioning
confidence: 99%
“…For some of them the final model included those with a PPV greater than 5% [ 18 , 21 ]. In others a subsequent study was performed for its validation by means of calculating false negatives in a random sample [ 19 ].…”
Section: Discussionmentioning
confidence: 99%